Determinants of Indonesian agricultural exports: A gravity model approach - Sugiharti, Lilik; Purwono, Rudi; Esquivias Padilla, Miguel Angel (International Journal of Psychosocial Rehabilitation, 2020)
This paper analyses determinants of agricultural exports and imports from Indonesia, including demand and supply factors capturing effects of income, market size, prices, and variables related to logistics, competitiveness, trade policy, and innovation. Trade creation and diversion effects are estimated as Indonesia experienced a deep liberalization of markets. A gravity model is employed to analyse agricultural exports disaggregated into raw goods and food. The dataset comprises 50 countries from 2007 until 2017. The results find trade creation effects for both categories, with larger effects in exports within agricultural raw goods, and higher trade creation through imports in food. Indonesia also experience trade expansion with non-free trade partners suggesting that demand variables (e.g. income, market size, sophistication) is a more important driver of growth rather than agreements. Price factors affect agricultural goods, with food products experience elastic price demand, while raw goods being affected by prices and exchange rate. Gains in competitiveness, logistic performance, and innovation is supporting agricultural exports (imports as well). The implementation of the FTAs should be critically evaluated with respect to food products as imports have expanded more rapidly than exports and domestic goods may have experience pressure from liberalization.